Prolapse of the vaginal vault - Ludmir, Abraham (2015)
The problem of vaginal vault, is a rare problem, but annoying, complicating a previous abdominal hysterectomy or Vaginal, conditioning upset the surgeon and the patient. What is questionable is the way of correction whether it should be abdominal or vaginal or a combination of both. We believe that the solution depends on each professional, according to the experience you have, and the conditions of the particular case; the gynecologist must be familiar with 1 or 2 techniques accepted vaginal or abdominal level; vaginal, is the natural technique, since the vagina is not retained in position by intraabdominal suspension only from above but for ligament support from below; but surgical repair is one of the most difficult problems in gynecological surgery; Although different techniques have appeared through the years, yet not completely satisfactory methods are reported.